The poverty implications of high oil prices in South Africa - Chitiga, Margaret; Fofana, Ismaël; Mabugu, Ramos (Cambridge University Press, 2012)
An energy-focused macro-micro approach is used to assess the poverty implications of government policy response to increases in international oil prices in South Africa. The first scenario assumes that increases in international oil prices are passed on to end users with no changes in government policy instruments. In this scenario, poverty indicators increase. The second scenario assumes that the world price increases are nullified by a price subsidy by the government. This scenario still leads to an increase in poverty as the beneficial price effect is cancelled out by a decline in households’ income induced by the financing method used. While revenue generated from a 50 per cent tax on windfall profit of the petroleum industry helps to minimize the loss in government revenue, it does not contribute to mitigating the increasing poverty trend, since the decline in saving and investment under this scenario restricts the country's growth, employment and income distribution perspectives.